The Impact of Scholarship on Contemporary “Gnosticism(s)”: A Case Study on the Apostolic Johannite Church and Jeremy Puma - Dillon, Matthew (International Journal for the Study of New Religions, 2018)
This article examines the impact of academic discourses on Neo-Gnosticism. The identities and ritual practices of Neo-Gnostics are constructed with reference to Gnostic Studies. Analysis of two case studies (the Apostolic Johannite Church and Jeremy Puma) shows how academic discourse legitimizes, challenges, or reforms Gnostic identity in the twenty-first century.